How Midwestern College students protected their families in the first year of COVID-19 - Myroniuk, Tyler W.; Teti, Michelle; David, Ifeolu; Schatz, Enid (Frontiers in Public Health, 2023)
Introduction College students routinely visit their families due to geographic proximity and their financial dependence. Consequently, the potential of transmitting COVID-19 from campus to their families’ homes is consequential. Family members are key sources of support for one another in nearly all matters but there is little research uncovering the mechanisms by which families have protected each other in the pandemic. Methods Through an exploratory qualitative study, we examined the perspectives of a diverse, randomly sampled, group of students from a Midwestern University (pseudonym), in a college town, to identify COVID-19 prevention practices with their family members. We interviewed 33 students between the end of December 2020 and mid-April 2021 and conducted a thematic analysis through an iterative process. Results Students navigated major differences in opinions and undertook significant actions in attempts to protect their family members from COVID-19 exposure. Students’ actions were rooted in the greater good of public health; prosocial behavior was on display. Discussion Larger public health initiatives could target the broader population by involving students as messengers.